Use of Telemedicine in Addiction Treatment: Current Practices and Organizational Implementation Characteristics - Todd Molfenter; Roger Brown; Andrew O’Neill; Ed Kopetsky; Alexander Toy (International Journal of Telemedicine and Applications)
Telemedicine applications offer innovative approaches for treating and reducing the effects of substance use disorders (SUDs). This analysis assessed the interest in and use of 11 telemedicine applications in a sample of 363 SUD organizations in the United States of America. Fifty percent of the organizations expressed high rates of interest in seven of the telemedicine applications, demonstrating the appeal of telemedicine within this field. The top three self-reported telemedicine applications being used were (1) computerized screening/assessments (44.6%), (2) telephone-based recovery supports (29.5%), and (3) telephone-based therapy (28.37%). The greatest gaps between interest and use were for (1) texting appointment reminders (55.2% differential), (2) mobile apps for posttreatment recovery (46.6% differential), and (3) recovery support chats (46.6% differential). A Latent Class Analysis (LCA) of the organizations’ telemedicine use behavior identified three groupings: “Innovators” that were using a range of technologies (n=27, 7.4%); “Technology Traditionalists” that limited their use to telephone, video, and web portal technologies (n=101, 27.8%); and “Low Tech” that had low overall technology use (n=235, 64.7%). Future studies should build on how telemedicine could be applied in SUD settings, organizational behaviors towards its adoption, and telemedicine’s effect on treatment adherence and clinical outcomes.